(untitled) - Ana Luísa C. Brasil Dozza; Abouch Valenty Krymchantowski (Arquivos de Neuro-Psiquiatria)
Objective To compare the adherence between monotherapy and politherapy in prophylactic migraine treatment. Method Five hundred consecutive patients with migraine from a tertiary center were retrospectively studied as to the number of preventive medications prescribed during the first visit. Adherence, defined as returning for the next consultation after 4 to 6 weeks and following the prescribed regimens, were also evaluated and compared between patients. Results 71.8% were women, and 6% of the patients did not receive any preventive medication, 11.4% received one drug, 22.2% two drugs, 41.4% three drugs, and 19% four drugs for the prevention of migraine. The overall adherence was 79.6%. Respectively, 73.7, 71.8, 82.6 and 86.3% of those who received the prescription of one, two, three and four drugs returned, complying with the treatment. Conclusion There is no difference in adherence to monotherapy or politherapy (one to four drugs) for the prophylaxis of migraine.